Pengaruh Media Diorama Lingkungan dalam Pembelajaran IPAS terhadap Keterampilan Berpikir Kritis Siswa Kelas V Sekolah Dasar - Nabila Faradhita Syah Fitri; Habudin Habudin; Oman Farhurohman; Rifqi Rijal; Wida Rachmiati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study was motivated by teachers' difficulties in implementing the curriculum and managing the learning process, particularly in developing students' critical thinking skills, as well as limited instructional time, which contributes to students' low critical thinking ability. This study aimed to analyze the effect of environmental diorama media on the critical thinking skills of fifth-grade students in Integrated Science and Social Studies (IPAS) learning at MI PKP JIS. The study employed a quantitative approach using a one-group pretest–posttest design. The sample consisted of 23 fifth-grade students from Class V A Sunan Kalijaga, selected through purposive sampling. Data were collected using pretest and posttest instruments and analyzed using the Wilcoxon Signed-Rank Test. The results showed a significance value of 0.000 (p < 0.05), with the mean score increasing from 81 to 98.8, representing a 21.9% improvement, while the N-Gain score reached 0.93, indicating a high category. These findings demonstrate that environmental diorama media effectively improves students' critical thinking skills in IPAS learning.